Grozeča prikazen mesta v stripu - Stanič, Ivan (Urbani izziv, 2003)
Graphic novels are a type of narrative, in which series of images are complemented with spoken words, thoughts of the depicted persons or additional explanatory descriptions next to the images, below them or in the images themselves. The text and images augment each other. The narrative is read and observed. The subject of the article is the representation of city in graphic novels and the depiction of city as the setting of stories, whatever their genre.
Keywords: mesta; motivi; podoba; stripi; upodobitev; vizualna umetnost